Sodium acetate ameliorates cisplatin-induced kidney injury in vitro and in vivo. (5th January 2023) - Zheng, Jun-Yao; Wang, Shao-Chuan; Tang, Sheau-Chung; Hsin, I-Lun; Kang, Yu-Ting; Hsu, Chih-Ting; Ou, Chu-Chyn; Ko, Jiunn-Liang
Abstract: Cisplatin is an effective chemotherapeutic drug against tumors. Studies often report on the improvement of kidney injury by probiotics or short-chain fatty acids (SCFAs); however, the effects of SCFAs on cisplatin-induced kidney injury are rarely studied. The aim of this study is to evaluate the function of sodium acetate on preventing cisplatin-induced kidney injury. Cell viability was detected by MTT assay. SA-β-gal staining was performed to investigate premature senescence. Reactive oxygen species (ROS) production was analyzed by H2 DCFDA staining. Propidium iodide (PI) staining was analyzed by cell cycle. Protein expression was determined by Western blot assay. Annexin Ⅴ/PI staining was used to investigate cisplatin-induced apoptosis. Tumor growth and kidney injury were evaluated in C57BL/6 mice. Sodium acetate ameliorated cisplatin-induced premature senescence and ROS production in SV40 MES-13 glomerular cells, NRK-52E renal tubular cells, and NRK-49F renal fibroblast cells. Cisplatin-induced cell cycle arrest was inhibited by sodium acetate in SV40 MES-13 and NRK-49F cells. Sodium acetate alleviated cisplatin-induced apoptosis in vivo and in vitro but not cisplatin-induced fibrosis. Our study demonstrated that sodium acetate inhibited cisplatin-induced premature senescence, cell cycle arrest, and apoptosis by attenuating ROS production. This strategy may be useful in the treatment of cisplatin-induced kidney injury. Graphical abstract: Image 1 Highlights: Sodium acetate inhibited cisplatin-induced premature senescence. Sodium acetate did not affect cisplatin-induced tumor toxicity. Sodium acetate downregulated cisplatin-induced cleaved caspase-3 expression. Sodium acetate downregulated cisplatin-induced apoptosis.